1999
DOI: 10.1063/1.124642
|View full text |Cite
|
Sign up to set email alerts
|

AgGaS 2 optical parametric oscillator continuously tunable from 3.9 to 11.3 μm

Abstract: This is the experimental realization of a silver gallium sulfide (AgGaS2) optical parametric oscillator (OPO) with a wide mid-IR tuning range. The singly resonant angle-tuned AgGaS2 type-II OPO was pumped by 1.06 μm pulses from a nanosecond Nd:YAG laser and yielded idler wave continuously tunable from 3.9 to 11.3 μm with a linewidth of 1 cm−1. The OPO threshold was 0.03 J/cm2 corresponding to sub-MW/cm2 pump intensity and sub-100 μJ pump energy. The slope and absolute quantum conversion efficiencies reached 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 16 publications
4
37
0
Order By: Relevance
“…Vodopyanov et al [21] have also demonstrated type-II phase-matched AgGaS 2 OPO pumped by nanosecond pulsed Nd:YAG laser and obtained linewidth of about 1 cm −1 in the spectral range of 3.8-11.0 μm.…”
Section: Employing Type-ii Phase Matchingmentioning
confidence: 93%
See 1 more Smart Citation
“…Vodopyanov et al [21] have also demonstrated type-II phase-matched AgGaS 2 OPO pumped by nanosecond pulsed Nd:YAG laser and obtained linewidth of about 1 cm −1 in the spectral range of 3.8-11.0 μm.…”
Section: Employing Type-ii Phase Matchingmentioning
confidence: 93%
“…Linewidth of the generated radiation can also be reduced to some extent using type-II phase matching due to steepness of the phase matching angle [20,21]. Brosenberg et al [20] have demonstrated type-II phase-matched BBO OPO pumped at 355 nm nanosecond radiations.…”
Section: Employing Type-ii Phase Matchingmentioning
confidence: 97%
“…A third approach, infrared lasers based on difference-frequency generation (DFG) in bulk non-linear crystals which has been developed already in the 1970s [25], is also experimentally difficult because of the need for high-power pumping lasers, and the problems related to phase matching in the non-linear materials when scanning broad spectral regions (more than a few 10 cm À1 ) [26,27]. Similar difficulties are also relevant for cw optical parametric oscillators (OPOs) [28,29].…”
Section: Introductionmentioning
confidence: 98%
“…Further improvement was limited by the damage of coating on cavity mirrors. The optical damage of cavity mirror and oscillating surface of the prism appeared at the input pump power density up to 34 MW/cm 2 , while no damage were seen both on the surfaces and inside of the crystal in OPO cavity, which we analyzed were contributed by the good growth, polishing and coating technique of the crystal comparing with other data [3][4][5][6]. This kind of cavity scheme can also be expected to benefit the linewidth and stability, which are going to be investigated in the near future.…”
mentioning
confidence: 99%
“…There are two effective methods to generate it: second harmonic generation (SHG) of CO 2 laser [1, 2] and optical parametric oscillator (OPO) [3][4][5][6][7][8][9][10]. The former has the limited tuning range at the atmospheric window, which is due to the limited tunable range of CO 2 laser.…”
mentioning
confidence: 99%